University Students’ Approaches to Nutrition - Vurgun, Hikmet; Eler, Nebahat (Progress in Nutrition, 2021)
The evaluation of nutritional habits is important for the development of healthy and quality life as well as for nutrition education for all individuals. In this study, we aimed to examine the relationship of the eating habits of the students of Manisa Celal Bayar University (MCBU) Sports Faculty and their gender, department at school, and status of being an active athlete. SPSS 20 software was used to analyze the data. In order to detect the difference between the nutritional habits of male and female students and the status of being a professional athlete, an independent t-test was used and to determine the relationship between nutritional habits and departments, one-way Anova test was used. Mean age, height, body weight, and body mass index (BMI) of the students were found to be 22.14 ± 2.22 years in girls, 23.89 ± 4.11 years in boys; 168.49 ± 7.38 cm in girls and 179.04 ± 12.56 cm in boys; 62.68 ± 11.85 kg in girls and 78.6 ± 10.64 kg in boys; 22.37 ± 3.63 (kg/m2) in girls and 24.67 ± 2.98 (kg/m2) in boys, respectively. Nutritional habits score (NHS) was found as 113.59 ± 27.96 in girls and 111.9 ± 19.31 in boys. There was no statistically significant relationship between gender and eating habits (p>0.05) and between male and female students' eating habits. In conclusion, it was found that there was no difference between the nutritional habits of the students of the Faculty of Sports Sciences of MCBU, when evaluated according to their gender, their department at school, and their status of being an active athlete. It was observed that students have neutral eating habits, that is, they practice healthy eating habits as much as unhealthy eating habits.